2017
DOI: 10.1186/s12905-017-0476-x
|View full text |Cite
|
Sign up to set email alerts
|

Levels, trends and correlates of unmet need for family planning among postpartum women in Indonesia: 2007–2015

Abstract: BackgroundAlthough Indonesia has relatively high contraceptive prevalence, postpartum family planning (PP-FP) has not been a particular point of emphasis. This article reports the results of analyses undertaken in order to (1) better understand levels and trends in unmet need for family planning among postpartum women, (2) assess the extent to which unmet need is concentrated among particular population sub-groups, and (3) assess the policy priority that PP-FP should have in relation to other interventions.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
3
18
1
1
Order By: Relevance
“…This study describes the prevalence of postpartum contraceptive use and skilled maternal healthcare among two representative samples (collected in 2011 and 2016) of married/in sexual union women in Ethiopia with a birth in the previous year. Our findings in both rounds are far lower than a finding from similar study in Indonesia (74%) [ 28 ]. In our 2011 sample, we found low contraceptive use; only 15% of women were protected from early pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
“…This study describes the prevalence of postpartum contraceptive use and skilled maternal healthcare among two representative samples (collected in 2011 and 2016) of married/in sexual union women in Ethiopia with a birth in the previous year. Our findings in both rounds are far lower than a finding from similar study in Indonesia (74%) [ 28 ]. In our 2011 sample, we found low contraceptive use; only 15% of women were protected from early pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
“…8 The analyses of data from the 2007 and 2012 Indonesia Demographic and Health Surveys (IDHS) and the 2015 PMA 2020 survey however reported total unmet need ranging from 23% to 28% which is lower compared to the findings from our study. 19 Lower rates of unmet need in comparison to our study were also reported by the studies conducted in Ethiopia 20 and Egypt. 21 The most popular modern contraceptive methods used by postpartum women were condoms (37.1%), Depo-Provera (29.3%) and pills (20.0%).…”
Section: Discussionsupporting
confidence: 86%
“…The proportion of women who use contraception declines with age; contraceptive use was highest among women < 24 and lowest among women > 35 [10, 35, 38, 42, 48, 49]. Postpartum contraceptive use was also higher among women who were more educated [11, 35, 40, 43, 44, 48, 5056], lived in urban residence [17, 40, 43, 51, 52], and had higher socio-economic status [40, 49, 51, 52]. However, in Sri Lanka contraceptive use was higher among women with low socio-economic status, which may be attributed to postnatal home visits by midwives who referred women for FP in this study [56].…”
Section: Resultsmentioning
confidence: 99%